2000
DOI: 10.1101/gad.177200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between C/EBPβ and FOG in eosinophil lineage commitment of multipotent hematopoietic progenitors

Abstract: The commitment of multipotent cells to particular developmental pathways requires specific changes in their transcription factor complement to generate the patterns of gene expression characteristic of specialized cell types. We have studied the role of the GATA cofactor Friend of GATA (FOG) in the differentiation of avian multipotent hematopoietic progenitors. We found that multipotent cells express high levels of FOG mRNA, which were rapidly down-regulated upon their C/EBP␤-mediated commitment to the eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
2
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 56 publications
11
80
2
1
Order By: Relevance
“…The ectopic expression of PU.1 and C/EBP also results in the commitment of hematopoietic progenitors to an eosinophilic lineage. [18][19][20] With respect to normal primary cells, it has been reported that murine B-cell precursor cells acquire the potential to differentiate into macrophage-like cells when they are transferred to myeloid culture conditions. 21 Normal murine early T progenitor cells also generate macrophages in cultures supplemented with conditioned medium from a thymic stromal cell line or in the presence of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic expression of PU.1 and C/EBP also results in the commitment of hematopoietic progenitors to an eosinophilic lineage. [18][19][20] With respect to normal primary cells, it has been reported that murine B-cell precursor cells acquire the potential to differentiate into macrophage-like cells when they are transferred to myeloid culture conditions. 21 Normal murine early T progenitor cells also generate macrophages in cultures supplemented with conditioned medium from a thymic stromal cell line or in the presence of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…65 Surprisingly, in eosinophil and mast cells, FOG-1 can antagonize GATA-1 activity thereby functioning as a corepressor within this cellular-dependent context. 62,66 The widely explored model of cell fate decisions during hematopoietic stem and progenitor development is based on the cross-antagonistic relationship between the PU.1 and GATA-1 transcription factors. However, once multi-potential progenitors differentiate into latter precursor stages such as monocyte/ granulocyte development, GATA-1 is no longer expressed and the process of cell specification depends on PU.1 and another primary lineage determinant, CEBPa.…”
Section: Pu1 and Gata-1 Interact During Early Hematopoietic Cell Decmentioning
confidence: 99%
“…A number of studies suggest that combinatorial interactions between hematopoietic factors regulate lineage selection. For example, Friend of GATA (FOG)-1 converts GATA-1 from an activator to a repressor of eosinophil lineage commitment (1). In addition, this complex is required for erythrocyte and megakaryocyte differentiation (2)(3)(4).…”
mentioning
confidence: 99%